Diseño, desarrollo y análisis de las propiedades psicométricas iniciales de una escala de capitales en emprendedores (CAPEM) en Colombia (2026)
Entrepreneurship has been a growing phenomenon in the world and in Colombia due to its ability to respond to conditions and needs present in the population. It is an economic proposal in the face of unemployment, poverty, armed conflict, and innovation. The role of the entrepreneur is crucial in the success of these ventures, and we can recognize the resources that they have through economic, social, cultural, symbolic and psychological capital. Therefore, the objective of this study was to design and analyze the initial psychometric properties of a scale of capitals in entrepreneurs in Colombia. Items were constructed from a table of dimensions, which were submitted to validation by judges.